LOVE PREREQUISITES IN PABLO NERUDA’S POEM IF YOU FORGET ME - Siti Khairunisah Zalukhu; M. Manugeren (Universitas Islam Sumatera Utara, 2020)
The poem is one of Pablo Neruda’s finest collections, containing undivided feelings for someone with picturesque comparisons with life and spiritual elements. The poem depicts a person’s selfless and pure love for another. It is about two choices a boy has given to a girl, whether the girl will forget him or come to him. While the first half of the poem is incredibly romantic and flattering, the third and fourth stanzas paint a very different picture, and they serve as a warning to Neruda’s mistress. The third stanza stands on its own, cautioning Neruda’s lover that if she stops loving him, he will do the same in return. It also begins the first in a string of ultimatums Neruda offers to his lover. The study is conducted by means of descriptive qualitative method, showing social pictures, in this case matters of love. The grand theory used is taken from Steinberg’s triangular theory of love. The results show that harmony in love could be obtained by means of intimacy, passion and commitment.